1978
DOI: 10.1210/endo-103-2-501
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Single Injection of Estradiol Valerate on the Hypothalamic Arcuate Nucleus and on Reproductive Function in the Female Rat*

Abstract: Young adult cyclic female rats were each injected with 2 mg estradiol valerate (EV) in sesame oil. Controls received an equivalent volume of sesame oil. Within 2 months after injection, most of the EV-treated animals showed persistent vaginal estrus and small polyfollicular ovaries as well as pathological changes in the hypothalamic arcuate nucleus. This pathological process was gradually progressive such that by 6 months after EV injection, the basal lateral region of the nucleus contained numerous reactive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
118
0

Year Published

1979
1979
1999
1999

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(131 citation statements)
references
References 15 publications
13
118
0
Order By: Relevance
“…This dose when administered to ovariectomized female rats produces a plasma level of oestradiol-17 p which is approximately double that of intact pro-oestrous rats (Cramer et al 1979). Thus in the present investigation the data of Brawer et al (1978) and Cramer et al (1979) would indicate that the 'average' plasma oestradiol-17 p level would be approximately double that of intact rats in pro-oestrous. In order to eliminate the possibility of endogenous oestrogen being a factor in the present studies, male rats were used throughout.…”
Section: (C) Drug Dosesmentioning
confidence: 48%
See 1 more Smart Citation
“…This dose when administered to ovariectomized female rats produces a plasma level of oestradiol-17 p which is approximately double that of intact pro-oestrous rats (Cramer et al 1979). Thus in the present investigation the data of Brawer et al (1978) and Cramer et al (1979) would indicate that the 'average' plasma oestradiol-17 p level would be approximately double that of intact rats in pro-oestrous. In order to eliminate the possibility of endogenous oestrogen being a factor in the present studies, male rats were used throughout.…”
Section: (C) Drug Dosesmentioning
confidence: 48%
“…This protocol has been shown to cause pathological changes in the medial basal hypothalamus of rats (Brawer and Sonnenschein 1975;Brawer and Naftolin 1979) and was thus considered a likely protocol to produce changes in the status of biogenic amines in the hypothalamic-median eminence region of the brain in the present studies. Brawer et al (1978) have further shown that the plasma levels of oestradiol-17 p in female rats treated with 2 mg oestradiol valerate are elevated to approximately 120 pg/ml 2 weeks after the injection but plateau at 30-40 pg/ml from 4 weeks after the injection. This latter plateau level is comparable to plasma levels of oestradiol-17 P in normal female rats in oestrus (Cramer et al 1979).…”
Section: (C) Drug Dosesmentioning
confidence: 87%
“…It is generally assumed that after maturity, exposure to endocrine disruptors does not permanently alter the functioning of hormone-responsive tissues. However, experimental studies in animals have shown permanent changes in brain (16) and vaginal epithelium (17) in females and prostate in males (18) (50,51). A major concern is that when women exposed in utero to estrogenic chemicals (DES and/or environmental pollutants that are estrogen agonists) reach the age at which the incidence of reproductive organ cancers normally increases, they will show a much higher incidence of cancer than unexposed individuals.…”
Section: Convincing Evidence Exists That a Variety Ofmentioning
confidence: 99%
“…However, in female rats the decline in the reproduct;ve system seems to be due to a decrease in the ability of the hypothalamus to release gonadotrophin releasing hormone (Meites et al, 1987;Finch, 1978). The onset of PE can occur as a consequence of natural aging (Ascheim, 1976;Schipper et al, 1981) or as a result of external influences such as exposure to continuous illumination or a single intramuscular dose of 2 mg estradiol valerate (EV; Brawer et al, 1978;Brawer et al, 1980). Administration of EV to young adult female rats results in axodendritic damage in the arcuate nucleus of the hypothalamus associated with the formation of myelin figures, synaptic loss and remodelling, increased numbers of reactive microglial cells containing phagocytosed material, and an accumulation of astrocytes…”
mentioning
confidence: 99%